Enhanced impacts of fipronil under a warming scenario on functional traits of paddy invertebrate communities - Naoto Ishiwaka; Masayoshi K. Hiraiwa; Teppei Nishiguchi; Koya Hashimoto; Kenji Tsuchiya; Francisco Sánchez-Bayo; Taku Kadoya; Daisuke Hayasaka (Environmental Pollution, 2026)

Indirect effects of insecticide exposure under warming conditions considering predator–prey interactions in a freshwater ecosystem - Naoto Ishiwaka; Masayoshi K. Hiraiwa; Koya Hashimoto; Kenji Tsuchiya; Kutta Doi; Kazane Yoshida; Taku Kadoya; Daisuke Hayasaka (Limnology, 2026)

Generation of canine gallbladder cholangiocyte organoids from healthy and gallbladder mucocele patient dogs for functional analysis of anion channels - Itsuma Nagao; Hirotaka Tomiyasu; Yuko Goto-Koshino; Kota Nakase; Takumi Tsuruta; Yuto Namiki; Ryuichiro Sato; Yu Takahashi; Yuko Hashimoto; Yosuke Takahashi; Naohiro Takahashi; James K. Chambers; et al. (The Veterinary Journal, 2025)

An expanded phylogenomic analysis of Heterolobosea reveals the deep relationships, non-canonical genetic codes, and cryptic flagellate stages in the group - Tomáš Pánek; Alexander K. Tice; Pia Corre; Pavla Hrubá; David Žihala; Ryoma Kamikawa; Euki Yazaki; Takashi Shiratori; Keitaro Kume; Tetsuo Hashimoto; Ken-ichiro Ishida; Miluše Hradilová; et al. (Molecular Phylogenetics and Evolution, 2025)

Surgical treatment of bovine nasal granuloma and an allergological exploration - Shogo Sato; Chihiro Kanno; Ryo Ando; Hisaya K Ono; Takuto Nakamura; Yota Hashimoto; Yosuke Maeda; Chun-Ho Park; Fumiaki Takahashi; Hiroaki Kawaguchi (Veterinary Research Communications, 2024)

Detection of environmental DNA of finless porpoise (Neophocaena asiaeorientalis) in Osaka Bay, Japan - Nagisa Hashimoto; Takashi Iwata; Natsumi Kihara; Kiyomi Nakamura; Masayuki K. Sakata; Toshifumi Minamoto (Conservation Genetics Resources, 2024)
Finless porpoises ( Neophocaena asiaeorientalis ) currently face population decline caused by significant human activities and are categorized as endangered on the International Union for Conservation of Nature (IUCN) Red List; however, information on their habitats is currently insufficient. Although conducting visual surveys to determine the distribution of cetaceans is common, visual observation of finless porpoises is challenging owing to their specific morphological and ecological characteristics. In this study, we developed an environmental DNA (eDNA) assay for species-specific detection of finless porpoises. To test the utility of the assay, we conducted a visual survey in parallel with an eDNA survey by collecting water samples from 50 sites throughout Osaka Bay. We visually found a finless porpoise at one location and detected eDNA at nine sites, including sites near the visual observation site and those with rare sightings of finless porpoises. Therefore, in this study, we suggest that the use of eDNA analysis for distribution surveys of finless porpoises will enable more efficient surveys. The proposed eDNA technique can not only be applied to the distribution surveys finless porpoises but also to those of other cetacean species.

Can warming accelerate the decline of Odonata species in experimental paddies due to insecticide fipronil exposure? - Naoto Ishiwaka; Koya Hashimoto; Masayoshi K. Hiraiwa; Francisco Sánchez-Bayo; Taku Kadoya; Daisuke Hayasaka (Environmental Pollution, 2024)

Towards a better future for biodiversity and people: Modelling Nature Futures - HyeJin Kim; Garry D. Peterson; William W.L. Cheung; Simon Ferrier; Rob Alkemade; Almut Arneth; Jan J. Kuiper; Sana Okayasu; Laura Pereira; Lilibeth A. Acosta; Rebecca Chaplin-Kramer; Eefje den Belder; et al. (Global Environmental Change, 2023)

Exploring Indigenous and Local Knowledge and Practices (ILKPs) in Traditional Jhum Cultivation for Localizing Sustainable Development Goals (SDGs): A Case Study from Zunheboto District of Nagaland, India - Rajarshi Dasgupta; Shalini Dhyani; Mrittika Basu; Rakesh Kadaverugu; Shizuka Hashimoto; Pankaj Kumar; Brian Alan Johnson; Yasuo Takahashi; Bijon K. Mitra; Ram Avtar; Priyanka Mitra (Environmental Management, 2023)

Actions to halt biodiversity loss generally benefit the climate - Yunne‐Jai Shin; Guy F. Midgley; Emma R. M. Archer; Almut Arneth; David K. A. Barnes; Lena Chan; Shizuka Hashimoto; Ove Hoegh‐Guldberg; Gregory Insarov; Paul Leadley; Lisa A. Levin; Hien T. Ngo; et al. (Global Change Biology, 2022)
The two most urgent and interlinked environmental challenges humanity faces are climate change and biodiversity loss. We are entering a pivotal decade for both the international biodiversity and climate change agendas with the sharpening of ambitious strategies and targets by the Convention on Biological Diversity and the United Nations Framework Convention on Climate Change. Within their respective Conventions, the biodiversity and climate interlinked challenges have largely been addressed separately. There is evidence that conservation actions that halt, slow or reverse biodiversity loss can simultaneously slow anthropogenic mediated climate change significantly. This review highlights conservation actions which have the largest potential for mitigation of climate change. We note that conservation actions have mainly synergistic benefits and few antagonistic trade‐offs with climate change mitigation. Specifically, we identify direct co‐benefits in 14 out of the 21 action targets of the draft post‐2020 global biodiversity framework of the Convention on Biological Diversity, notwithstanding the many indirect links that can also support both biodiversity conservation and climate change mitigation. These relationships are context and scale‐dependent; therefore, we showcase examples of local biodiversity conservation actions that can be incentivized, guided and prioritized by global objectives and targets. The close interlinkages between biodiversity, climate change mitigation, other nature's contributions to people and good quality of life are seldom as integrated as they should be in management and policy. This review aims to re‐emphasize the vital relationships between biodiversity conservation actions and climate change mitigation in a timely manner, in support to major Conferences of Parties that are about to negotiate strategic frameworks and international goals for the decades to come.

Clinical significance of Aspergillus species isolated from respiratory specimens in patients with Mycobacterium avium complex lung disease - K. Furuuchi; A. Ito; T. Hashimoto; S. Kumagai; T. Ishida (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Structural and Morphometric Comparison of Lower Incisors in PACAP-Deficient and Wild-Type Mice - B. Sandor; K. Fintor; D. Reglodi; D. B. Fulop; Z. Helyes; I. Szanto; P. Nagy; H. Hashimoto; A. Tamas (Journal of Molecular Neuroscience, 2016)

Relationships between capture-site characteristics and capture levels of the invasive mongoose on Amami-Oshima Island, Japan - H. Komine; K. Takeshita; S. Abe; T. Ishikawa; M. Kimura; T. Hashimoto; K. Kitaura; T. Morosawa; K. Seki; K. Kaji (Biological Invasions, 2016)

Magnetically-modified natural biogenic iron oxides for organic xenobiotics removal - I. Safarik; J. Filip; K. Horska; M. Nowakova; J. Tucek; M. Safarikova; H. Hashimoto; J. Takada; R. Zboril (International Journal of Environmental Science and Technology, 2015)

Structural and Morphometric Comparison of the Molar Teeth in Pre-eruptive Developmental Stage of PACAP-Deficient and Wild-Type Mice - B. Sandor; K. Fintor; Sz. Felszeghy; T. Juhasz; D. Reglodi; L. Mark; P. Kiss; A. Jungling; B. D. Fulop; A. D. Nagy; H. Hashimoto; R. Zakany; et al. (Journal of Molecular Neuroscience, 2014)

Examination of Calcium-Binding Protein Expression in the Inner Ear of Wild-Type, Heterozygous and Homozygous Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP)-Knockout Mice in Kanamycin-Induced Ototoxicity - A. Nemeth; K. Szabadfi; B. Fulop; D. Reglodi; P. Kiss; J. Farkas; B. Szalontai; R. Gabriel; H. Hashimoto; A. Tamas (Neurotoxicity Research, 2014)

A large hydrothermal reservoir beneath Taal Volcano (Philippines) revealed by magnetotelluric resistivity survey: 2D resistivity modeling - Y. Yamaya; P. K. B. Alanis; A. Takeuchi; J. M. Cordon; T. Mogi; T. Hashimoto; Y. Sasai; T. Nagao (Bulletin of Volcanology, 2013)

PACAP is an Endogenous Protective Factor—Insights from PACAP-Deficient Mice - D. Reglodi; P. Kiss; K. Szabadfi; T. Atlasz; R. Gabriel; G. Horvath; P. Szakaly; B. Sandor; A. Lubics; E. Laszlo; J. Farkas; A. Matkovits; et al. (Journal of Molecular Neuroscience, 2012)

Characteristics and osteogenic differentiation of stem/progenitor cells in the human dental follicle analyzed by gene expression profiling - H. Aonuma; N. Ogura; K. Takahashi; Y. Fujimoto; S. Iwai; H. Hashimoto; K. Ito; Y. Kamino; T. Kondoh (Cell and Tissue Research, 2012)

‘Better off alone than in bad company’: agonistic colour display in mimetic juveniles of two ephippid species - B. Barros; Y. Sakai; H. Hashimoto; K. Gushima; M. Vallinoto (Journal of Fish Biology, 2012)
Comparative field observations of agonistic interactions in juvenile leaf‐mimicking Platax orbicularis and Chaetodipterus faber (Ephippidae) were conducted in coastal waters of the Pacific and Atlantic Oceans. Similar agonistic behaviour was observed in the two species, in which individuals stopped displaying their mimetic colouration during encounters with conspecifics, to display conspicuous colours, such as transverse stripes along the body. These events were observed occasionally, almost invariably in individuals of smaller body size. Larger‐bodied individuals of both species spent less time in agonistic displays. The absolute size of the fish, however, did not appear to affect the outcome of the encounter, suggesting that dominance is a temporary condition, based on the relative size of the opponents during encounters.

Comparative Examination of Inner Ear in Wild Type and Pituitary Adenylate Cyclase Activating Polypeptide (PACAP)-Deficient Mice - A. Tamas; K. Szabadfi; A. Nemeth; B. Fulop; P. Kiss; T. Atlasz; R. Gabriel; H. Hashimoto; A. Baba; N. Shintani; Zs. Helyes; D. Reglodi (Neurotoxicity Research, 2012)

Effects of renal function on the pharmacokinetics and pharmacodynamics of prophylactic cefazolin in cardiothoracic surgery - T. Kosaka; K. Hosokawa; N. Shime; F. Taniguchi; T. Kokufu; S. Hashimoto; H. Fujiwara; H. Yaku; N. Sugioka; K. Okada; N. Fujita (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Mice Deficient in Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) are More Susceptible to Retinal Ischemic Injury In Vivo - K. Szabadfi; T. Atlasz; P. Kiss; B. Danyadi; A. Tamas; Zs. Helyes; H. Hashimoto; N. Shintani; A. Baba; G. Toth; R. Gabriel; D. Reglodi (Neurotoxicity Research, 2012)

Androgen Receptor Overexpression Is Neuroprotective in Experimental Stroke - Patricia Ayala; Masayoshi Uchida; Kozaburo Akiyoshi; Jian Cheng; Joel Hashimoto; Taiping Jia; Oline K. Ronnekleiv; Stephanie J. Murphy; Kristine M. Wiren; Patricia D. Hurn (Translational Stroke Research, 2011)

Ion microprobe (SHRIMP) U–Pb dating of Upper Cretaceous volcanics from the northern Lord Howe Rise, Tasman Sea - K. Higgins; T. Hashimoto; G. Fraser; N. Rollet; J. Colwell (Australian Journal of Earth Sciences, 2011)

Evolution of host breadth in broad interactions: mycorrhizal specificity in East Asian and North American rattlesnake plantains (Goodyera spp.) and their fungal hosts - RICHARD P. SHEFFERSON; CHARLES C. COWDEN; MELISSA K. MCCORMICK; TOMOHISA YUKAWA; YUKI OGURA-TSUJITA; TOSHIMASA HASHIMOTO (Molecular Ecology, 2010)

Antifouling properties of tough gels against barnacles in a long-term marine environment experiment - T. Murosaki; T. Noguchi; K. Hashimoto; A. Kakugo; T. Kurokawa; J. Saito; Y. M. Chen; H. Furukawa; J. P. Gong (Biofouling, 2009)

Nucleotide sequence analysis of seven Japanese isolates of Plantago asiatica mosaic virus (PlAMV): a unique potexvirus with significantly high genomic and biological variability within the species - K. Komatsu; Y. Yamaji; J. Ozeki; M. Hashimoto; S. Kagiwada; S. Takahashi; S. Namba (Archives of Virology, 2008)

Complete nucleotide sequence of asparagus virus 3 - M. Hashimoto; J. Ozeki; K. Komatsu; H. Senshu; S. Kagiwada; T. Mori; Y. Yamaji; S. Namba (Archives of Virology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genome sequence of a Japanese isolate of Radish mosaic virus: the first complete nucleotide sequence of a crucifer-infecting comovirus - K. Komatsu; M. Hashimoto; K. Maejima; J. Ozeki; S. Kagiwada; S. Takahashi; Y. Yamaji; S. Namba (Archives of Virology, 2007)

Hypoxia-induced hyaluronan synthesis by articular chondrocytes: the role of nitric oxide - K. Hashimoto; K. Fukuda; K. Yamazaki; N. Yamamoto; T. Matsushita; S. Hayakawa; H. Munakata; C. Hamanishi (Inflammation Research, 2006)

Horizontal and Vertical Distribution of Estrogenic Activities in Sediments and Waters from Tokyo Bay, Japan - S. Hashimoto; A. Horiuchi; T. Yoshimoto; M. Nakao; H. Omura; Y. Kato; H. Tanaka; K. Kannan; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2005)

Current Levels of Dioxins in Surface Soils from Santiago, Chile - Y. Takazawa; R. Verdugo; P. Richter; K. Kitamura; J.-W. Choi; S. Hashimoto; H. Ito; Y. Shibata; M. Morita (Bulletin of Environmental Contamination and Toxicology, 2004)

Centripetal bias on preparation for smooth pursuit eye movements based on the anticipation - H. Tabata; K. Hashimoto; N. Inaba; K. Kawano (Experimental Brain Research, 2004)

Development of PCR-based SNP markers for rice blast resistance genes at the Piz locus - K. Hayashi; N. Hashimoto; M. Daigen; I. Ashikawa (Theoretical and Applied Genetics, 2004)

Sleeping mound construction using coral fragments by the rockmover wrasse - S. Takayanagi; Y. Sakai; H. Hashimoto; K. Gushima (Journal of Fish Biology, 2003)
The rockmover wrasse Novaculichthys taeniourus was observed using coral fragments for mound construction on the reefs of Kuchierabu‐jima Island, Japan. The wrasse heaped between four and 71 pieces of coral fragments on each sand mound, and dived into the mound just before sunset. Coral fragments may facilitate the retention of sleeping sites under competition with other sand‐diving wrasses.

Genetic similarity of outbreak populations of crown-of-thorns starfish (Acanthaster planci) that were 15years apart in Okinawa, Japan - M. Katoh; K. Hashimoto (Coral Reefs, 2003)

Peripheral nerve regeneration through alginate gel: analysis of early outgrowth and late increase in diameter of regenerating axons - T. Hashimoto; Y. Suzuki; M. Kitada; K. Kataoka; S. Wu; K. Suzuki; K. Endo; Y. Nishimura; C. Ide (Experimental Brain Research, 2002)

Molecular taxonomy of vestimentiferans of the western Pacific and their phylogenetic relationship to species of the eastern Pacific - Kojima S.; Ohta S.; Yamamoto T.; Miura T.; Fujiwara Y.; Fujikura K.; Hashimoto J. (Marine Biology, 2002)

Differentiation in the status of self-incompatibility among Calibrachoa species (Solanaceae) - T. Tsukamoto; T. Ando; H. Watanabe; H. Kokubun; G. Hashimoto; U. Sakazaki; E. Surez; E. Marchesi; K. Oyama; T. Kao (Journal of Plant Research, 2002)

3. Histaminergic mechanisms in the brain¶Possible involvement of the chorda tympani nerve in stimulation of the histaminergic system by leptin - T. Morimoto-Ishizuka; Y. Treesukosol; Y. Yamamoto; K. Yamamoto; T. Hashimoto; A. Yamatodani (Inflammation Research, 2002)

Critical involvement of CD40 in protection against herpes simplex virus infection in a murine model of genital herpes - K. Inagaki-Ohara; T. Kawabe; Y. Hasegawa; N. Hashimoto; Y. Nishiyama (Archives of Virology, 2002)

Differential effects of bacterial toxins on mitogenic actions of sodium fluoride and those of aluminum fluoride in human TE85 osteosarcoma cells - Hideki Hashimoto; K.-H. William Lau (Molecular and Cellular Biochemistry, 2001)

Construction of a high-resolution linkage map of a rice brown planthopper (Nilaparvata lugens Stål) resistance gene bph2 - H. Murai; Z. Hashimoto; P. N. Sharma; T. Shimizu; K. Murata; S. Takumi; N. Mori; S. Kawasaki; C. Nakamura (Theoretical and Applied Genetics, 2001)

A method for detecting myocardial abnormality by using a total current-vector calculated from ST-segment deviation of a magnetocardiogram signal - A. Kandori; H. Kanzaki; K. Miyatake; S. Hashimoto; S. Itoh; N. Tanaka; T. Miyashita; K. Tsukada (Medical & Biological Engineering & Computing, 2001)

A method for detecting myocardial abnormality by using a current-ratio map calculated from an exercise-induced magnetocardiogram - A. Kandori; H. Kanzaki; K. Miyatake; S. Hashimoto; S. Itoh; N. Tanaka; T. Miyashita; K. Tsukada (Medical & Biological Engineering & Computing, 2001)

Structure of the infected cell protein 0 gene of canine herpesvirus - M. Miyoshi; M. Takiguchi; J. Yasuda; A. Hashimoto; A. Takada; K. Okazaki; H. Kida (Archives of Virology, 2000)

Genetic contribution of the BAT2 gene microsatellite polymorphism to the age-at-onset of insulin-dependent diabetes mellitus - M. Hashimoto; N. Nakamura; H. Obayashi; F. Kimura; A. Moriwaki; G. Hasegawa; H. Shigeta; Y. Kitagawa; K. Nakano; M. Kondo; M. Ohta; M. Nishimura (Human Genetics, 1999)

Genetic contribution of the BAT2 gene microsatellite polymorphism to the age-at-onset of insulin-dependent diabetes mellitus - M. Hashimoto; N. Nakamura; H. Obayashi; F. Kimura; A. Moriwaki; G. Hasegawa; H. Shigeta; Y. Kitagawa; K. Nakano; M. Kondo; M. Ohta; M. Nishimura (Human Genetics, 1999)

A Comparison of the Plasma Fructose Concentrations in Dogs and Cats and Changes in the Fructose Concentrations in Dogs Following Intravenous Administration of Fructose - T. Arai; K. Hashimoto; H. Muzutani; T. Kawabata; T. Sako; T. Washizu (Veterinary Research Communications, 1999)

Visualization of microtubules in living cells of transgenicArabidopsis thaliana - K. Ueda; T. Matsuyama; T. Hashimoto (Protoplasma, 1999)

Structure of the immediate early gene of canine herpesvirus - M. Miyoshi; M. Takiguchi; J. Yasuda; A. Hashimoto; A. Takada; K. Okazaki; H. Kida (Archives of Virology, 1999)

Interaction of citrus juices with pranidipine, a new 1,4-dihydropyridine calcium antagonist, in healthy subjects - K. Hashimoto; T. Shirafuji; H. Sekino; O. Matsuoka; H. Sekino; O. Onnagawa; T. Okamoto; S. Kudo; J. Azuma (European Journal of Clinical Pharmacology, 1998)

Enhanced human tumor cell transplantability in a new congenic immunodeficient mouse; KSN-BNX - Y. Ishigaki; K. Yasuda; N. Hashimoto; H. Nikaido; O. Nikaido; J. -I. Hayakawa (Folia Microbiologica, 1998)

Effect of root exudate fractions from P-deficient and P-sufficient onion plants on root colonisation by the arbuscular mycorrhizal fungus Gigaspora margarita - K. Tawaraya; Kazuko Hashimoto; Tadao Wagatsuma (Mycorrhiza, 1998)

Urine-associated horizontal transmission of Seoul virus among rats - H. Kariwa; M. Fujiki; K. Yoshimatsu; J. Arikawa; I. Takashima; N. Hashimoto (Archives of Virology, 1998)

Urine-associated horizontal transmission of Seoul virus among rats - H. Kariwa; M. Fujiki; K. Yoshimatsu; J. Arikawa; I. Takashima; N. Hashimoto (Archives of Virology, 1998)

Molecular systematics of vestimentiferan tubeworms from hydrothermal vents and cold-water seeps - M. B. Black; K. M. Halanych; P. A. Y. Maas; W. R. Hoeh; J. Hashimoto; D. Desbruyères; R. A. Lutz; R. C. Vrijenhoek (Marine Biology, 1997)

Effects of carp serum on the growth of goldfish fin cells in early passage - H. Hashimoto; H. Toyohara; Y. Yokoyama; M. Sakaguchi; K. Ozato; Y. Wakamatsu (Journal of Fish Biology, 1997)
The culture medium supplemented with carp serum and fetal bovine serum (FBS) promoted cell growth significantly and induced morphological change of goldfish fin cells in early passage as compared to the medium containing FBS alone. However, these effects were not observed in RBCF‐1, a cell line established from the goldfish fin. The sensitivity of the cells in early passage to carp serum suggests the following possibilities: (1) cells in early passage retain the ability to respond to growth‐promoting factors specifically included in carp serum; and (2) this ability is lost during the process of long‐term culture and/or long‐term culture in FBS eliminates cell groups showing high dependency of cell growth on carp serum.

Modes of Seoul virus infections: persistency in newborn rats and transiency in adult rats - H. Kariwa; M. Kimura; S. Yoshizumi; J. Arikawa; K. Yoshimatsu; I. Takashima; N. Hashimoto (Archives of Virology, 1996)

Lactoferrin-mediated protection of the host from murine cytomegalovirus infection by a T-cell-dependent augmentation of natural killer cell activity - K. Shimizu; H. Matsuzawa; K. Okada; S. Tazume; S. Dosako; Y. Kawasaki; K. Hashimoto; Y. Koga (Archives of Virology, 1996)

Heat shock induces HIV-1 replication in chronically infected promyelocyte cell line OM10.1 - K. Hashimoto; M. Baba; K. Gohnai; M. Sato; S. Shigeta (Archives of Virology, 1996)

Analysis of target organs for the latency of murine cytomegalovirus DNA using specific pathogen free and germfree mice - H. Matsuzawa; K. Shimizu; K. Okada; K. Ando; K. Hashimoto; Y. Koga (Archives of Virology, 1995)

Molecular cloning and sequence determination of the peplomer protein gene of feline infectious peritonitis virus type I - K. Motokawa; T. Hohdatsu; C. Aizawa; H. Koyama; H. Hashimoto (Archives of Virology, 1995)

Unusual splice sites in the E1A?E1B cotranscripts synthesized in adenovirus type 40-infected A549 cells - S. Ishida; Y. Fujinaga; K. Fujinaga; N. Sakamoto; S. Hashimoto (Archives of Virology, 1994)

Antibody-dependent enhancement of hantavirus infection in macrophage cell lines - J. -S. Yao; H. Kariwa; I. Takashima; K. Yoshimatsu; J. Arikawa; N. Hashimoto (Archives of Virology, 1992)

Protective role of antigenic sites on the envelope protein of Hantaan virus defined by monoclonal antibodies - J. Arikawa; J. -S. Yao; K. Yoshimatsu; I. Takashima; N. Hashimoto (Archives of Virology, 1992)

Preparation of Japanese encephalitis virus nonstructural protein NS1 obtained from culture fluid of JEV-infected Vero cells - T. Lee; K. Watanabe; C. Aizawa; A. Nomoto; H. Hashimoto (Archives of Virology, 1991)

Role of maternal antibody in protection from hemorrhagic fever with renal syndrome virus infection in rats - X. -K. Zhang; I. Takashima; N. Hashimoto (Archives of Virology, 1988)

Development of a psoriasis-like syndrome following lithium therapy - K. Hanada; M. Tasaki; I. Hashimoto; M. Sone; T. Yamaguchi (Biological Trace Element Research, 1987)

Epidemiological studies of hemorrhagic fever with renal syndrome (HFRS) related virus infection among urban rats in Hokkaido, Japan - J. Arikawa; I. Takashima; N. Hashimoto; K. Takahashi; K. Yagi; K. Hattori (Archives of Virology, 1986)

Getah virus inAedes vexans nipponii andCulex tritaeniorhynchus: Vector susceptibility and ability to transmit - I. Takashima; N. Hashimoto; J. Arikawa; K. Matsumoto (Archives of Virology, 1983)

Enhanced production of interferon by ultraviolet irradiation and pretreatment with interferon in human diploid cells stimulated with polyinosinate-polycytidilate - H. Komatsu; N. Maehara; K. Shimoda; H. Hashimoto; T. Mori; T. Lee; S. Makino; M. Matumoto (Archives of Virology, 1982)

Isolation of the structural proteins of western equine encephalitis virus by isoelectric focusing - K. Hashimoto; B. Simizu (Archives of Virology, 1979)

Maturation defect of a temperature-sensitive mutant of western equine encephalitis virus - K. Hashimoto; K. Suzuki; B. Simizu (Archives of Virology, 1977)

Quantitative description of end plate current and its reconstruction - H. Yagi; T. Hashimoto; K. Sugimoto (Biological Cybernetics, 1977)

Effect of cordycepin on the replication of western equine encephalitis virus - K. Hashimoto; B. Simizu (Archives of Virology, 1976)

Effect of alkaline maintenance medium upon the growth of rabies virus in chick embryo cells - K. Yoshino; Taka Kishie; Mitsue Hashimoto; K. Yanagi (Archives of Virology, 1975)